2022
DOI: 10.3390/lubricants10030046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preload on the Vibrations of EHL Angular Contact Ball Bearings: Theoretical and Experimental Results

Abstract: The vibrations of a shaft in rotary mechanical systems supported by angular contact ball bearings are investigated theoretically and experimentally for various preloads in this paper. In the theoretical part of the study, a dynamic bearing model is presented, a rigid shaft supported by EHL angular contact bearing has been modelled as 5 DoF. Non-linear equations of motion are solved numerically by the Runge–Kutta method. In the second part of the study, an experimental setup that enables performing different op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…When the rotor is supported asymmetrically, only one side of the bearing generates excitation energy, while under symmetrical support, the bearings on both sides generate VC excitation energy at the same speed. In the coupled model, the increase in radial load and clearance exacerbates VC vibration, while rotor imbalance has a smaller impact on VC vibration. The results are consistent with the literature, 1315 verifying the rationality of the model.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When the rotor is supported asymmetrically, only one side of the bearing generates excitation energy, while under symmetrical support, the bearings on both sides generate VC excitation energy at the same speed. In the coupled model, the increase in radial load and clearance exacerbates VC vibration, while rotor imbalance has a smaller impact on VC vibration. The results are consistent with the literature, 1315 verifying the rationality of the model.…”
Section: Discussionsupporting
confidence: 92%
“…In the coupled model, the increase in radial load and clearance exacerbates VC vibration, while rotor imbalance has a smaller impact on VC vibration. The results are consistent with the literature, 1315 verifying the rationality of the model.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When the bearing is in the healthy stage, H d = 0. When the bearing is in the failure stage, unlike in [19,24,25] which regarded the failure shape as a rectangular pit, the contact deformation between the rolling element and the defect edge is ignored. In this study, a fault profile as shown in figure 2 is established to maximize the actual situation of bearing failure.…”
Section: Virtual Entity (Ve) Modelmentioning
confidence: 99%
“…In the model, each ball has six degrees of freedom (DOFs), meaning that the three-dimensional motion of balls is considered. Bal [19] presented a multiple-DOF angular contact bearing dynamic model to examine effect of preload on the vibration of shaftbearing system. Qin et al [20] developed a novel dynamic model for a faulty rolling bearing, in which the DOFs of all movable components are considered.…”
Section: Introductionmentioning
confidence: 99%